2000
DOI: 10.1046/j.1365-2249.2000.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-alpha (TNF-α) enhances lymphocyte migration into rheumatoid synovial tissue transplanted into severe combined immunodeficient (SCID) mice

Abstract: SUMMARYAdhesion mechanisms play a major role in the recruitment of peripheral blood lymphocytes (PBL) which characteristically infiltrate rheumatoid arthritis (RA) synovium and other chronically inflamed tissues. Through a sequential series of complex integrated adhesion and signalling events,`multistep model of migration', specific subsets of PBL are recruited into inflamed tissues. In this process both leucocyte receptors and microvascular endothelial (MVE) counter-receptors play a critical role. The MVE in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
53
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 31 publications
5
53
0
2
Order By: Relevance
“…Lymphodepletion has been reported in several similar models. 15,38,39 Likewise, Wahid and colleagues 39 concluded that in the absence of T cells producing the Figure 11. CFSE-labeled human T cells traffic specifically into RA synovial grafts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lymphodepletion has been reported in several similar models. 15,38,39 Likewise, Wahid and colleagues 39 concluded that in the absence of T cells producing the Figure 11. CFSE-labeled human T cells traffic specifically into RA synovial grafts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in previous models in which cell suspensions or small pieces of synovium were implanted, lymphodepletion was routinely observed. 15,21,38,39 In some of these models the synovial tissue was implanted under the kidney capsule or in an ear pouch. It is possible that the location of the graft played a role in the lymphodepletion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, standardized pieces of synovial tissue from RA patients are transplanted subcutaneously on the back or under the renal capsule of immunodeficient mice (9,10 (14,15). Adoptive T cell transfer into the RA synovium SCID mouse model augmented this cytokine production (14).…”
mentioning
confidence: 99%